(untitled) (Research, Society and Development, 2022)
The current research aims at analyzing fish farming production in the Western Mesoregion of Parana State and its significance within Brazilian data, highlighting the types of fish in the main states and cities involved in the activity. Research data were obtained from FAO, from IBGE’s Municipal Livestock (Aquiculture) Production Survey, data provided by DERAL/SEAB and in recent publications on the studied subject. Quantitative data were presented through boxes, images, and figures, with their respective analyses. Among the main results, it is observed that Brazil produced 551.8 thousand tons of fish in 2020, also, that Parana state is the largest producer, being responsible for 24.8% of that number, and Western Mesoregion represents 82% of the state’s production with 112,470 tons. The research highlight is in Tilapia fish production, considering that the country produced 343.5 thousand tons of Tilapia in 2020, considering that Parana produced 134.32 thousand tons of Tilapia and represents 96% of the state’s production and Parana’s Western Mesoregion accounted for 111 thousand tons distributed in its 50 cities and having 10 of them highlighted, with 77% of that production, summing up to 85,198 tons produced in the highlighted municipalities in 2020. Analyzing DERAL data, it is observed that in those 10 municipalities there is a gross production value of Tilapia of 620 billion, which represents 59% of production value in Parana in 2021.